HUBUNGAN PENGGUNAAN ALAT PELINDUNG DIRI DENGAN KEJADIAN TINEA PEDIS PADA PETUGAS KEBERSIHAN DPU CIPTA KARYA KECAMATAN UMBULSARI - Ahmad Efrizal Ammrullah; Mahmud Ady Yuwanto (Jurnal Kesehatan dr. Soebandi, 2017)
The prevalence of dermatophytosis in Asia reaches 35.6% (Kumar et al, 2011). Based on patient visits in hospitals throughout Indonesia, there were 192,414 visits, of whom 22,076 were new cases and were ranked 3 out of the top 10 outpatients in 2011 (MOH, 2012). This study aims to determine the relationship of the use of personal protective equipment with the occurrence of tinea pedis in cleaning workers public works inventions created by Umbulsari District. The research design used is descriptive correlational study of the relationship between variables using a cross sectional approach. The sample in this study was taken by means of a total sampling that is all janitor DPU copyright works Umbulsari District using observation sheet measurement tools. The results of this study were analyzed using the Lambda Correlation Test. The results of the analysis found that there is a relationship between the use of personal protective equipment with the incidence of tinea pedis of significance (0.037 <0.05) with a positive direction which means that the more adherent to the use of PPE the smaller the risk of tinea pedis. It is recommended for cleaning staff to be more obedient to the use of PPE in order to reduce the risk of tinea pedis and for the DPU department of public works to provide facilities related to PPE to the janitor